Predicting the outcome of surgery for the proximal interphalangeal joint in Dupuytren's disease. - Misra, A; Jain, A; Ghazanfar, R; Johnston, T; Nanchahal, J (2007)
PURPOSE: We prospectively studied the outcome of limited Dupuytren's fasciectomy, in combination with joint release if necessary, for disease involving 49 proximal interphalangeal joints (PIPJs) to identify factors that predispose to recurrent PIPJ contracture. METHODS: Thirty-seven patients were treated over a 4-year period. The flexion contracture of the PIPJ was measured before surgery, immediately after surgery, and at more than 1 year after surgery. RESULTS: A mean preoperative flexion contracture of 67 degrees +/- 22 degrees was corrected to 6 degrees +/- 10 degrees at the time of surgery and 25 degrees +/- 25 degrees at the follow-up evaluation. There was a positive correlation between the severity of the preoperative flexion contracture and recurrent deformity, with a preoperative contracture greater than 60 degrees leading to significantly worse outcome. Incomplete correction of PIPJ flexion contracture during surgery and poor postoperative compliance with therapy were also associated with worse recurrent joint contractures. The digit involved and the necessity for joint release did not significantly affect outcome. CONCLUSIONS: In the absence of recurrent Dupuytren's disease, severe preoperative deformity, incomplete correction at surgery, and noncompliance with therapy predispose patients to worse PIPJ contracture. TYPE OF STUDY/LEVEL OF EVIDENCE: Prognostic II.